HUBUNGAN USIA DAN PARITAS DENGAN KEJADIAN HIPEREMESIS GRAVIDARUM DI RSUD RADEN MATTAHER JAMBI - Rini Sahari (MIDWIFERY HEALTH JOURNAL, 2019)
One of the causes of trimester 1 pregnant women often experience excessive nausea and vomiting. Some pregnant women can not cope with nausea, vomiting, until hyperemesis gravidarum continues, disrupting daily life, causing disruption of fluid and electrolyte balance. Based on data from the Raden Mattaher Jambi Hospital in 2016 the number of data on patients with Hyperemesis Gravidarum was 68 cases, in 2017 the number of patients with 60 cases and in 2018 the number of data on patients with Hyperemesis Gtavidarum 74 cases in the Raden Mattaher Regional Hospital in Jambi Province. The purpose of the study was to determine the relationship of age and parity with the occurrence of hyperemesis gravidarum in Raden Mattaher Regional Hospital in Jambi Province in 2018. This study uses a case control research method with a total sample of 148 respondents consisting of 74 cases and 74 cases. The sampling technique was taken by random sampling technique for cases and simple random sampling for control. Data analysis used chi-square to find out the relationship between age and parity with the occurrence of Hyperemesis Gravidarum. between the age of the Hyperemesis Gravidarum event, and the Parity to the Hyperemesis Gravidarum event the results of data analysis obtained p-value = 0.023 and OR = 0.422 the conclusion of this study is that there is a relationship between age and parity with the incidence of hyperemesis Gravidarum.